1999
DOI: 10.1039/a906048k
|View full text |Cite
|
Sign up to set email alerts
|

Polymer supported cobalt carbonyl complexes as novel traceless alkyne linkers for solid-phase synthesis

Abstract: The immobilisation of functionalised alkynes onto 'polymerbound triphenylphosphine', their chemical manipulation and subsequent release has been demonstrated for the first time, thus illustrating that cobalt carbonyl complexes can be used as 'traceless' p-alkyne linkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…In einem neuen Zugang zu Schutzgruppen‐Linkern des Typs C (siehe Abbildung 1) beschreiben Gibson et al die Immobilisierung von Alkinsubstraten an polymergebundenem Triphenylphosphan über π‐Wechselwirkungen zu Dicobaltcarbonyl‐Komplexen (Tabelle 4). Die Produkte mit einer PACT‐Csp≡Csp‐Spur werden durch oxidative Dekomplexierung mit Luftsauerstoff abgelöst 14…”
Section: Bildung Von Alkinenunclassified
“…In einem neuen Zugang zu Schutzgruppen‐Linkern des Typs C (siehe Abbildung 1) beschreiben Gibson et al die Immobilisierung von Alkinsubstraten an polymergebundenem Triphenylphosphan über π‐Wechselwirkungen zu Dicobaltcarbonyl‐Komplexen (Tabelle 4). Die Produkte mit einer PACT‐Csp≡Csp‐Spur werden durch oxidative Dekomplexierung mit Luftsauerstoff abgelöst 14…”
Section: Bildung Von Alkinenunclassified
“…In a novel approach to a protecting group linker of Type C (see Figure 1) Gibson and co‐workers describe the immobilization of alkyne substrates to polymer‐bound triphenylphosphane through π interactions to dicobalt carbonyl complexes (Table 4). The products are liberated by aerial oxidative decomplexation with a PACT Csp≡Csp vestige 14…”
Section: Alkyne Formationmentioning
confidence: 99%
“…The alkyne-cobalt complex can be subsequently immobilized onto a solid-supported phosphine. It has been demonstrated that alkyne-cobalt complexes react selectively with triphenylphosphine (PPh 3 ) and solid-supported PPh 3 2223. We envisioned using an approach similar to the latter case to selectively remove the alkyne from the vast majority of native phospholipids which are washed away.…”
mentioning
confidence: 99%